Study on the Freeze-Thaw Problems in the Winter Construction of the Lianghekou Earth-Core Rockfill Dam and the Countermeasures for Prevention - Qihao Yu; Xiu-Ling Ren; Pan Yue; Gui-Ke Zhang; Jun-Feng Wang; Yan-Hu Mu; En-Long Liu (Advances in Materials Science and Engineering)
Winter construction in seasonally frozen soil areas is inevitable. The variation of ambient temperature causes the freeze-thaw of the filling soils and its impact is significant, and whether the countermeasures can be effectively established and adopted is particularly important for the management and control of the construction quality of the project. This paper conducts systematic research based on the winter construction process of the dam core wall of the Lianghekou Hydropower Station, which is the third highest earth-core rockfill dam in the world under construction. The results show that for the construction site in the seasonally frozen soil area, there is a development process of the short-term frozen soils for the filling soils under the environment with low temperature in winter. The soil underwent a high-frequency freeze-thaw process wherein it was frozen at night and completely thawed during the day. During the freezing process, a large number of thin-layered segregated ice developed inside the soil to form a thin-layered or integral cryostructure, which will have an adverse effect on the engineering properties and the quality of the filling soils. And, the field tests demonstrate that the filling compaction degree of the frozen soils is difficult to meet the designed requirements. In order to effectively cope with the adverse effect of the freeze-thaw on the construction quality during the construction process, based on the analysis of the freeze-thaw characteristics of soils and its influence, and the energy exchange process of soils on-site, the principles and methods for establishing the freeze prevention system during the winter construction process are established, and a comprehensive monitoring system suitable for on-site is established in this paper. This research will provide an important reference for the scientific management and efficiency improvement of the winter construction process of the dams in cold regions.